Discursive Power: Trade Over Health in CARICOM Food Labelling Policy - Hinton, Lucy (Frontiers in Communication, 2022)
Moving towards a more sustainable, healthier, and equitable food future requires a significant system transformation. Policies to achieve this transformation are notoriously difficult to achieve, especially where actors with conflicts of interest are involved in governance. In this paper, I analyze how corporate actors frame issues inside a process to develop Front-of-Pack Labelling across the Caribbean. Focusing on three major framing strategies, I show how food companies argued (1) (falsely) that FOPL would privilege Chilean food suppliers; (2) that FOPL would constitute a major transgression of international trade law; and (3) that a regional public health organization (the Pan-American Health Organization) is an illegitimate influence on the policy. Together, these three framing strategies change the policy problem construction to one of trade rather than public health. I argue that the resulting narrative is both a product and a function of the discursive power food companies wield in the standard-setting process and provide empirical detail about how food companies act to prevent policy attempts facilitating food systems transformation.